2003
DOI: 10.2298/sarh0312454a
|View full text |Cite
|
Sign up to set email alerts
|

The first case of isolation of malassezia globosa in our country

Abstract: Today is known that genus Malassezia includes seven species: M. furfur, M. sympodialis, M. obtusa, M. globosa, M. restricta, M. sloofflae and M. pachydermatis, but role of each of the species in the pathogenesis of disease has not been elucidated yet, so further laboratory isolation and identification are necessary. We report the first case of isolation of Malassezia globosa in Serbia (Belgrade), in a patient suffering from Pityriasis versicolor. Identification of M. globosa was based on macroscopic, microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
0
1
Order By: Relevance
“…Thus, in these subjects, metabolic products and antigens of Malassezia can lead to the development of SD as a result of immunopathology and could explain why the number of Malassezia does not correlate with Malassezia SD severity . Some studies showed that determination of Malassezia 's metabolic products and antigens could be an important prognostic parameter for skin diseases caused by this yeast …”
Section: Discussioncontrasting
confidence: 84%
“…Thus, in these subjects, metabolic products and antigens of Malassezia can lead to the development of SD as a result of immunopathology and could explain why the number of Malassezia does not correlate with Malassezia SD severity . Some studies showed that determination of Malassezia 's metabolic products and antigens could be an important prognostic parameter for skin diseases caused by this yeast …”
Section: Discussioncontrasting
confidence: 84%